Relationship between rule of law and tax revenues: dynamic panel data analysis (Public Sector Economics - submission site, 2022)
Tax revenue has been declining in most countries recently. Therefore, to better understand the reasons behind this, some studies focus on supply factors, while few studies focus on demand factors. In this context, this study aims to analyse the impact of rule of law on tax revenues in 59 countries by using the panel dana method over the period 2002-2018 considering the level of economic development. This study is different from previous studies in several respects. Firstly, it uses a different and more comprehensive index to measure rule of law. Secondly, we focus on the economic level of countries, which is a crucial factor for measuring efficiency of the rule of law. The results show that the effect of rule of law on tax revenues varies based on the level of economic development of the countries.